O07.1 Novel use of venue-specific codes to track impact of a campaign to increase awareness and use of an online HIV/STI testing service (getcheckedonline) among gay and bisexual men in vancouver, canada. (8th July 2017) - Salway, Travis; Kwag, Michael; Edward, Joshua; Haag, Devon; Bondyra, Mark; Grace, Daniel; Cox, Joseph; Moore, David; Trussler, Terry; Hart, Trevor; Shannon, Kate; Shoveller, Jean; et al.
Abstract : Introduction: GetCheckedOnline (GCO) is an online HIV/STI testing service where clients create an account, complete a risk assessment, print a lab form, submit specimens at a lab and get results online or by phone. From April-Sept 2015 the JustMakesSense (JMS) campaign aimed to increase awareness and use of GCO among gay and bisexual men (GBMSM) in Vancouver. JMS promoted GCO's convenience and used multiple physical and online venues (social media, sex-seeking websites/apps, gay bars, events), with venue-specific codes to create accounts which we used to measure campaign impact. Methods: Individuals were tracked from JMS website visits to GCO account creation and testing using venue-specific GCO access codes. Awareness of JMS and GCO was measured using a Pride survey (Aug 2015) and post-campaign perceptions of JMS and GCO gathered through key informant interviews and focus groups. Results: Over 6 months, 18 273 views of the JMS campaign page led to 659 (4%) visits of the GCO website. 177 visitors created GCO accounts and by Dec 2015, 43 (24%) tested at least once (none positive). 58% of GCO accounts/52% of tests were from ads on sex-seeking websites/apps (vs. 1%/0% from social media, 12%/9% from physical venues, and 29%/39% source unknown). 25% of 114 GBMSM surveyed were aware of JMS and GCO. Interviews/focus groups with 7 participants suggested GCO may not have been perceived as convenient given existing accessible, culturally appropriate HIV/STI testing services for GBMSM in Vancouver, and that GCO may better suit men living outside urban Vancouver or with privacy concerns that make visiting gay-branded testing services less likely. Conclusion: Our novel use of unique tracking codes permitted detailed per-venue evaluation of the JMS campaign; greatest uptake was from sex-seeking website/app ads vs. other venues. While JMS views were high and 1 in 4 men were aware of GCO, GCO use was low possibly owing to the availability of relatively convenient in-clinic testing services in the city. Promotion outside Vancouver and of the privacy of GCO may increase uptake among GBMSM.